Quantitative Research: A Successful Investigation in Natural and Social Sciences - Mohajan, Haradhan Kumar (Journal of Economic Development, Environment and People, 2020)
Research is the framework used for the planning, implementation, and analysis of a study. The proper choice of a suitable research methodology can provide an effective and successful original research. A researcher can reach his/her expected goal by following any kind of research methodology. Quantitative research methodology is preferred by many researchers. This article presents and analyzes the design of quantitative research. It also discusses the proper use and the components of quantitative research methodology. It is used to quantify attitudes, opinions, behaviors, and other defined variables and generalize results from a larger sample population by the way of generating numerical data. The purpose of this study is to provide some important fundamental concepts of quantitative research to the common readers for the development of their future projects, articles and/or theses. An attempt has been taken here to study the aspects of the quantitative research methodology in some detail.